THE EFFECTIVENESS OF THE INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) IN ADDRESSING HUMAN TRAFFICKING AGAINST INDONESIAN MIGRANT WORKERS IN MALAYSIA POST-COVID-19 - Rizkika Dwi (Mediasi: Journal of International Relations, 2021)
This study analyzes the effectiveness of the International Organization for Migration (IOM) as an intergovernmental organization that focuses on migration issues in combating human trafficking of Indonesian migrant workers in Malaysia during the Covid-19 pandemic. IOM basically does not have the authority to eradicate the problem of human trafficking, but because this problem stems from irregular migration, IOM is trying to help the Indonesian government together with various partners to overcome this problem. In its role, IOM established the Counter Trafficking Unit (CTU) which focuses on addressing human trafficking. CTU activities are based on the "3P+Partnership" strategic approach. The research objective in this study is to analyze the effectiveness of international organizations, namely, IOM in overcoming human trafficking of Indonesian migrant workers working in Malaysia after Covid-19. The analytical knife used in this research is the theory of the effectiveness of international organizations and the concept of human security. The method used in this research is a qualitative method with analytical descriptive writing techniques. The result of this research is that IOM is not effective in overcoming human trafficking against Indonesian migrant workers in Malaysia. This can be proven through the dimensions of output, outcome, and impact. IOM can fulfill the output and outcome dimensions, but in the impact dimension, IOM has not been able to provide changes in Indonesian policy and IOM's handling efforts are not focused on migrant workers in Malaysia, but victims of human trafficking in general. In addition, data on human trafficking victims of migrant workers in Malaysia is inefficient and does not show the accuracy of the numbers.